2014
DOI: 10.1002/ana.24241
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord gray matter atrophy correlates with multiple sclerosis disability

Abstract: Objective In multiple sclerosis (MS) cerebral gray matter (GM) atrophy correlates more strongly than white matter (WM) atrophy with disability. The corresponding relationships in the spinal cord (SC) are unknown due to technical limitations in assessing SCGM atrophy. Using phase sensitive inversion recovery (PSIR) MRI, we determined the association of the SCGM and SCWM areas with MS disability and disease type. Methods 113 MS patients and 20 healthy controls were examined at 3T with a PSIR sequence acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
171
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(184 citation statements)
references
References 55 publications
12
171
1
Order By: Relevance
“…For example, cross-sectional data demonstrated that EDSS is highly correlated with grey matter volume in the cervical and thoracic cord, independent of brain volume. 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…For example, cross-sectional data demonstrated that EDSS is highly correlated with grey matter volume in the cervical and thoracic cord, independent of brain volume. 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…GM atrophy linked to multiple sclerosis (MS), as demonstrated recently based on volumetric measurements (Kearney et al, 2014;Schlaeger et al, 2014), to ALS (Cohen-Adad et al, 2013), or aging as recently studied in vivo through relative and absolute gray matter area and measurements (Fradet et al, 2014).…”
Section: Spinal Cord Tbm For Age-related Changes Characterizationmentioning
confidence: 99%
“…Atrophy of the cerebellum on the other hand, driven by volume loss of the cerebellar cortex, has been shown to be a landmark for conversion to the secondary progressive disease state (Calabrese et al, 2013). The clinical relevance of cervical cord atrophy is related to its high anatomicalfunctional vulnerability, which has been emphasized in several recent studies (Bonati et al, 2011;Kearney et al, 2014;Lukas et al, 2015;Oh et al, 2013;Schlaeger et al, 2014;Valsasina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%